2011
DOI: 10.1242/jcs.072058
|View full text |Cite
|
Sign up to set email alerts
|

LSR defines cell corners for tricellular tight junction formation in epithelial cells

Abstract: SummaryEpithelial cell contacts consist of not only bicellular contacts but also tricellular contacts, where the corners of three cells meet. At tricellular contacts, tight junctions (TJs) generate specialized structures termed tricellular TJs (tTJs) to seal the intercellular space. Tricellulin is the only known molecular component of tTJs and is involved in the formation of tTJs, as well as in the normal epithelial barrier function. However, the detailed molecular mechanism of how tTJs are formed and maintain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
255
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 219 publications
(286 citation statements)
references
References 33 publications
13
255
1
Order By: Relevance
“…Recently, it has been shown that unique molecular components are required to seal the paracellular barrier at the contact points of three cells. These tricellular junctional complexes are made up of lipolysis-stimulated receptor (LSR), which is required to localize marveld2 to tricellular adhesions (Masuda et al 2011). It remains unclear what the nature of the size/charge-selective pore is formed by the specific composition tight junction proteins expressed by CNS ECs, and whether the permeability of this pore is static or whether it is dynamically altered in response to neuronal activity.…”
Section: Tight Junctionsmentioning
confidence: 99%
“…Recently, it has been shown that unique molecular components are required to seal the paracellular barrier at the contact points of three cells. These tricellular junctional complexes are made up of lipolysis-stimulated receptor (LSR), which is required to localize marveld2 to tricellular adhesions (Masuda et al 2011). It remains unclear what the nature of the size/charge-selective pore is formed by the specific composition tight junction proteins expressed by CNS ECs, and whether the permeability of this pore is static or whether it is dynamically altered in response to neuronal activity.…”
Section: Tight Junctionsmentioning
confidence: 99%
“…Two types of integral membrane proteins, tricellulin (Ikenouchi et al, 2005) and angulin family proteins, which include angulin-1/LSR, angulin-2/ILDR1, and angulin-3/ILDR2 (Higashi et al, 2013;Masuda et al, 2011), have been identified as specific molecular components of tTJs. Tricellulin is a member of the TAMP family containing occludin with four transmembrane domains (Ikenouchi et al, 2005;Raleigh et al, 2010;Steed et al, 2009), while angulins are singlepass membrane proteins with an Ig-like domain (Masuda et al, 2011;Higashi et al, 2013). Notably, angulins recruit tricellulin to TCs and at least one of the angulin family members is expressed in each epithelium with tricellulin (Higashi et al, 2013;Masuda et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Tricellulin is a member of the TAMP family containing occludin with four transmembrane domains (Ikenouchi et al, 2005;Raleigh et al, 2010;Steed et al, 2009), while angulins are singlepass membrane proteins with an Ig-like domain (Masuda et al, 2011;Higashi et al, 2013). Notably, angulins recruit tricellulin to TCs and at least one of the angulin family members is expressed in each epithelium with tricellulin (Higashi et al, 2013;Masuda et al, 2011). shRNA-mediated depletion of tricellulin or angulin-1/LSR in cultured epithelial cells revealed that these molecules are required for normal tTJ formation as well as the full barrier function of epithelial cellular sheets (Higashi et al, 2013;Ikenouchi et al, 2005;Masuda et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas bicellular TJs contain biochemical complexes including occludin, claudins (cLs), and junctional adhesion molecules, 5) tricellular TJs include at least tricellulin and members of the angulin family. [6][7][8] Pharmacologic and pathologic research has revealed that cLs offer considerable potential as targets for the delivery of various therapeutic compounds. For instance, cL-1-knockout mice showed increased epidermal permeability to solutes.…”
Section: Introductionmentioning
confidence: 99%